VALUASI EKONOMI HUTAN MANGROVE AKIBAT KONVERSI LAHAN DI TAMAN WISATA ALAM PANTAI PANJANG DAN PULAU BAAI, BENGKULU - , Nike Anggraini ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The importance of knowing economic value of mangrove forest resources as one of policy input factor is a step in maintaining the sustanability of coastal ecosystem. This research uses economic valuation to calculate lost benefits value of mangrove forest ecosystem which experienced land conversion in area Natural Tourism Park of Panjang Beach and Baai Island Bengkulu. This research aims to: (1) analyzed spacial-temporal conversion of mangrove forest in research area and its causative factors